Italo Calvino and the organizational imagination: Reading social organization through urban metaphors. Issue 2 (14th March 2016) - Case, Peter; Gaggiotti, Hugo
Abstract : This article explores the way in which uses or abuses of urban metaphors can inform differing polities and ethics of human organization. From its earliest inception, the city has taken on a metaphorical significance for human communities; being, at one and the same time, a discursive textual product of culture and, reciprocally, a provider of artefacts and architecture that produces culture and meaning. The city can be interpreted as a trope that operates bidirectionally in cultural terms. It is a sign that can be worked to serve the principles of both metonymy and synecdoche. In metonymical or reductive form, the city has the propensity to become weighty and deadening. The work of Michael Porter on competitive strategy is invoked to illustrate this effect. In the guise of synecdoche, on the other hand, the city offers imaginative potential. Drawing inspiration from the literary works of Italo Calvino (in particular, his novel Invisible Cities ), the article attempts to reveal the fecundity of the city for interpreting technologically mediated organizational life. Calvino's emphasis on the principle of 'lightness' provides a link to the social theoretical writing of Boltanski and Chiapello on the 'projective city'. A synthesis of these two stylistically different literatures yields a novel way of critically approaching and understanding the reticular form and emerging ethics of contemporary human organization.